Frequency of Hematoma Formation Subsequent to Injection of Dental Local Anesthetics In Children - Kuster, Curtis G. (1984)
This study investigated the frequency of hematoma formation subsequent to injection of dental local anesthetics in 4,134 children, 3 to 13 years of age. Hematoma formation occurred following 0.1% of the injections, all being buccal infiltrations of maxillary molars. This represents a 0.4% incidence of hematoma formation subsequent to this injection. There was no age specificity in hematoma formation, occurring in one 5 year old, one 7 year old, one 8 year old, one 10 year old, and one 11 year old.